Analisis Pengaruh Economic Value Added (Eva) Dan Rasio Likuiditas Terhadap Perubahan Laba Perusahaan Pada Perusahaan Manufaktur Sektor Food And Baverage Tahun 2012-2014 - Ningsih, Furri Rahayu; , Kussudyarsana, S.E., M.Si (2017)
ABSTRACT This research aims to know the influence of the Economic Value Added (EVA) and liquidity ratios of the company profit to changes on the company's Manufacturing Sector Food And Baverage in 2012-2014. This type of research is explanatory research research. The population in this research is the manufacturing companies listed on the Indonesia stock exchange period 2012-2014. The sample in this research is the manufacturing sector food and baverage listed on the Indonesia stock exchange period 2012-2014. Sampling with purposive sampling. The data used in the form of secondary data. Data analysis technique used was multiple linear regression analysis. Based on the results of the regression testing of partially variable EVA to changes in enterprise manufacturing sector food and baverage years 2012-2014. QR (X2) individually have no effect significantly changes the corporate profits of the company. CR (X3) individually effect significantly changes the corporate profits of the company. Keywords: EVA, QR, CR